PRINCIPLES OF PASSING AND DOCUMENTING INSTRUCTIONS ON SAFETY TECHNIQUES - Muradov , Sirojiddin Husan o‘g‘li; Zayniyev , Ulfat Utkir o‘g‘li (Educational Research in Universal Sciences, 2023)
The article covers the issues of training and testing the knowledge of all employees on labor protection, regardless of the type of work.